Characterization of a defensin from the oyster Crassostrea gigas. Recombinant production, folding, solution structure, antimicrobial activities, and gene expression. - Gueguen, Yannick; Herpin, Amaury; Aumelas, André; Garnier, Julien; Fievet, Julie; Escoubas, Jean-Michel; Bulet, Philippe; Gonzalez, Marcelo; Lelong, Christophe; Favrel, Pascal; Bachère, Evelyne (Journal of Biological Chemistry, 2006)
International audience In invertebrates, defensins were found in arthropods and in the mussels. Here, we report for the first time the identification and characterization of a defensin (Cg-Def) from an oyster. Cg-def mRNA was isolated from Crassostrea gigas mantle using an expressed sequence tag approach. To gain insight into potential roles of Cg-Def in oyster immunity, we produced the recombinant peptide in Escherichia coli, characterized its antimicrobial activities, determined its solution structure by NMR spectroscopy, and quantified its gene expression in vivo following bacterial challenge of oysters. Recombinant Cg-Def was active in vitro against Gram-positive bacteria but showed no or limited activities against Gram-negative bacteria and fungi. The activity of Cg-Def was retained in vitro at a salt concentration similar to that of seawater. The Cg-Def structure shares the so-called cystine-stabilized alpha-beta motif (CS-alphabeta) with arthropod defensins but is characterized by the presence of an additional disulfide bond, as previously observed in the mussel defensin (MGD-1). Nevertheless, despite a similar global fold, the Cg-Def and MGD-1 structures mainly differ by the size of their loops and by the presence of two aspartic residues in Cg-Def. Distribution of Cg-def mRNA in various oyster tissues revealed that Cg-def is mainly expressed in mantle edge where it was detected by mass spectrometry analyses. Furthermore, we observed that the Cg-def messenger concentration was unchanged after bacterial challenge. Our results suggest that Cg-def gene is continuously expressed in the mantle and would play a key role in oyster by providing a first line of defense against pathogen colonization.